2016
DOI: 10.1371/journal.pone.0166546
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Taiwan Performance-Based Instrumental Activities of Daily Living (TPIADL), a Performance- Based Measurement of Instrumental Activities of Daily Living for Patients with Vascular Cognitive Impairment

Abstract: ObjectivePatients with cerebrovascular diseases often presented both cognitive and physical impairment. Disability in everyday functioning involving cognitive impairment among patients may be hard to completely rely on informants’ reports, as their reports may be confounded with physical impairment. The aim of this study was to validate a performance-based measure of functional assessment, the Taiwan Performance-Based Instrumental Activities of Daily Living (TPIADL), for vascular cognitive impairment (VCI) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A decline in cognitive function can lead to deficiencies in decision-making ability 30) and subsequent ethical problems in both the clarity of the scale items and in obtaining informed consent. Laudisio et al 4) observed normal and higher cognitive function adequacy in individuals with HMT scores above 7, while Chen et al 31) reported that cognitive disorders negatively affected IADL performance. For these reasons, the present study used HMT scores of ≥ 8 one as an inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
“…A decline in cognitive function can lead to deficiencies in decision-making ability 30) and subsequent ethical problems in both the clarity of the scale items and in obtaining informed consent. Laudisio et al 4) observed normal and higher cognitive function adequacy in individuals with HMT scores above 7, while Chen et al 31) reported that cognitive disorders negatively affected IADL performance. For these reasons, the present study used HMT scores of ≥ 8 one as an inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Because the assessment has an administration duration of 3–5 min and because only simple test materials are required, the task is suitable for clinical assessment in studies of large samples. It also has an established validity, indicating that the TPIADL is sensitive to impairment ( Chen et al, 2015 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Keywords Subcortical ischemic vascular disease; Alzheimer's disease; Cognition; Motor function; Activities of daily life; Instrumental activities of daily life; White matter hyperintensities Neuropsychiatry (London) (2018) 8(2) 558Research Yen-Hsuan Hsu care strategy [14].Several studies have reported ADL profiles and their relevant impact among patients with AD [15][16][17]. However, the functional profiles and determining factors in individuals with SIVD have yet to be fully elucidated [18][19][20], and comparisons of these two prevalent subtypes of dementia are even more limited [19][20]. Therefore, the aims of the current study were to compare the profiles of ADL performance between patients with SIVD and AD subtypes, and to analyze predictors of daily functional performance in different subtypes of dementia by examining the associations between clinical factors, cognitive/motor function, and WMHs.…”
mentioning
confidence: 99%